Endoscopic Transsphenoidal Hypophisectomy versus Microscopic Transsphenoidal Surgery in the Treatment of Pituitary Adenomas: Evaluation of Results in Terms of Ophthalmic Affection - Sumkovski, Robert; Filipce, Venko; Kocevski, Ivica; Micunovic, Micun (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Neurophthalmologic examination is part of the baseline evaluation of patients with pituitary lesions. The neuro-ophthalmologist quantifies and evaluates the impact that the sellar lesion has on afferent and efferent visual pathways, contributes to the determination of tumor growth dynamics, and monitors the success and possible complications. In cases of vision loss, blurring, damage, or double vision as symptoms of a clinical presentation, the neuro-ophthalmologist is often the first to recognize and define the pituitary lesion. AIM: The aims of this study are as follows: First, to determine the comparative difference and value of the axis/width of the field of vision in the comparable resection technologies, i.e. fully endoscopic and microscopic/microscopic-assisted hypophysectomy; and second, the extend of resection in both technologies compared with post-operative outcome analysis. METHODS: The study was designed as a retrospective-prospective clinical trial in the period of 2011–2017. This study enrolled 85 patients, 46 of whom were treated with a microscopic resection, and 39 patients treated only with endoscopic transsphenoidal resection of pituitary adenomas as the subject of this study. RESULTS: The results of our analysis showed that the achievement of complete, radical, and subtotal resection is significantly higher in the endoscopic technique compared to the microscopic technique. Essentially, better lighting, better viewing angle with no “blind spots,” and a perfected toolkit of instruments are the objective factors for progress. CONCLUSION: The results of our study, comparing the endoscopic version of the microscopic transnasal, transsphenoidal resection of pituitary adenomas, during the period 2010–2018, have unequivocally shown that the endoscopic transnasal transsphenoidal procedure is rational, effective, efficient, and above all safe technique, with a number of favorable advantages that allow for a higher degree of surgical radicality.